Integrated multi-omics profiling reveals neutrophil extracellular traps potentiate Aortic dissection progression - Yu-Fei Zhao; Zi-Ang Zuo; Zhe-Yun Li; Ye Yuan; Shi-Chai Hong; Wei-Guo Fu; Bin Zhou; Li-Xin Wang (Nature Communications)
Abstract Adverse aortic remodeling increases the risk of aorta-related adverse events (AAEs) after thoracic endovascular aortic repair (TEVAR) and affects the overall prognosis of aortic dissection (AD). It is imperative to delve into the exploration of prognostic indicators to streamline the identification of individuals at elevated risk for postoperative AAEs, and therapeutic targets to optimize the efficacy of TEVAR for patients with AD. Here, we perform proteomic and single-cell transcriptomic analyses of peripheral blood and aortic lesions, respectively, from patients with AD and healthy subjects. The integrated multi-omics profiling identifies that highly phenotype-associated macrophages orchestrate neutrophil extracellular traps (NETs) through CXCL3/CXCR2 axis, thereby promoting the development of AD. Increased NETs formation is a defining feature of systemic immunity and aortic microenvironment of AD. Inhibiting NETs formation through the blockade of citrullinated histone H3 or CXCL3/CXCR2 axis ameliorates the progression and rupture of aortic dissection in male mice. The plasma level of citrullinated histone H3 predicts AAEs following endovascular therapy, facilitating the risk stratification and prognostic evaluation for patients with AD.